Law Enforcement Against Illegal Parking Attendants Reviewed From Cirebon City Regulation No.11 Of 2019 Concerning the Implementation of Parking - Farikah, Mia; Mubarok , Alfin; Ardiyansyah , Salwa; Rahman , Alip; Harliyanto , Rois (Journal of Legal and Cultural Analytics, 2025)
In the modern era, the ownership of private vehicles is increasing because of their convenience and practicality. Therefore, parking lots are needed. The problem of illegal parking often occurs in small and large cities, including Cirebon City. This journal intends to analyze the effectiveness of law enforcement against illegal parking attendants, as reviewed from Regional Regulation No. 11 of 2019 concerning the Implementation of Parking. This writing's research method is empirical juridical. It examines the applicable regulations and collects data through observation and interviews to analyze the law's implementation in the field. The study results show that Regional Regulation No. 11 of 2019 concerning Parking has not run effectively, which is caused by several obstacles such as limited personnel, lack of infrastructure, and fewer firm witnesses, so that illegal parking attendants do not feel the deterrent effect. even though the Transportation Department has provided regular guidance and socialization to the parking attendants and the community. Crackdowns against illegal parking perpetrators are minimal and tend to be constructive rather than heavily sanctioned. As a result, illegal parking still occurs in many places in Cirebon City, causing traffic congestion and irregularities. To ensure effective regulation implementation, the government's future efforts need to be focused on the capacity of its personnel, stricter sanctions enforcement, and increasing legal awareness of the public and parking attendants.